Beyond the visual: panoramatic attractions in the 1900 World's Fair. Issue 4 (2nd October 2017) - Hernández Barbosa, Sonsoles
Abstract : The 1900 World's Fair congregated a large number of attractions that revolutionised the tradition of panorama. These attractions were complex devices: often, they incorporated highly technological advances and played a vital role in the emergence of an entertainment culture. In this paper, I attempt to reconstruct three of these devices through an examination of archival material: the Maréorama, which followed the tradition of simulating a journey; the Globe Céleste, which was similar to today's planetariums; and the Phono-cinéma-théâtre, which, following the example of the Théâtroscope, was based on the representation of a stage performance. All three of these combined visual, sound and scenic effects. I will try to interpret how the visual experience was complemented by other sensory stimuli, such as sounds and smells, as well as by the immersive nature of the devices. My aim is to investigate what these attractions, as material objects, may have contributed to overcoming a merely visual conceptualisation of perception. Also, the paper explores how the fin de siècle culture appears to have assumed this new perspective, as reflected by its objects, and examines its relationship with the incipient mass culture.